Gastrointestinal findings in children with Down syndrome: Is there an early sign for Celiac disease? - Kocamaz, Halil; Işıkay, Sedat (My University, 2018)
Aim: To investigate the prevalence of celiac disease (CD) among children with Down’s syndrome (DS) and its association with gastrointestinal symptoms and other accompanying diseases. Methods: The study was consisted of regular trisomy 21 patients who were under follow-up in our department. The age, gender, gastrointestinal symptoms (abdominal pain, constipation, diarrhea, abdominal distension, vomiting, flatulence, and unsatisfactory weight gain/weight loss) and accompanying diseases were recorded. Anti-tissue transglutaminase (anti-tTG) immunoglobulin A (Ig A) levels were analyzed in all cases. Serologically positive patients were referred to a pediatric gastroenterologist for intestinal biopsy. Results: Totally 98 children with a mean age of 3.22.81 years (range: 2-13 years) diagnosed with the DS were included in this study. Among study participants, 46 (46.9%) were female. Among study participants, 3 (3.1%) had positive anti-tTG IgA results and endoscopic biopsies revealed the diagnosis of Marsh type 3b CD in all of them. In correlation analysis, hypothyroidism (p0.03) and presence of diarrhea (p0.04) significantly correlated with the CD presence among children with the DS. Diarrhea increased the risk for 1.50 times (0.67-3.34) while hypothyroidism increased the risk for 2.75 times (0.55-13.67) among patients with DS. Conclusion: Clinicians should be aware of an increased prevalence of CD among patients with DS especially in children with diarrhea and/or hypothyroidism.

Amaç: Down sendromlu (DS) çocuklarda çölyak hastalığının (ÇH) sıklığı ile gastrointestinal semptomlar ve eşlik eden diğer hastalıklarla birlikteliğini saptamak. Yöntemler: Çalışmaya kliniğimizde takip edilen regüler trizomi 21 olan hastalar alındı. Yaş, cinsiyet, gastrointestinal semptomlar (karın ağrısı, kabızlık, diyare, abdominal distansiyon, kusma, şişkinlik ve kilo alımı / kilo kaybı) ve eşlik eden ek hastalıklar kaydedildi. Tüm olgularda anti-doku transglutaminaz (anti-tTG) immünoglobulin A (IgA) düzeyleri analiz edildi. Çölyak serolojisi pozitif saptanan hastalara, çocuk gastroenteroloji uzmanı tarafından ince bağırsak biyopsisi yapıldı. Bulgular: Çalışmaya yaş ortalaması 3,2 2,81 yıl (2-13 yıl) olan 98 çocuk alındı. Hastaların 46’sı (% 46,9) kızdı. Hastaların 3'ünde (% 3,1) anti-tTG IgA pozitifliği vardı ve endoskopik biyopsilerin hepsinde Marsh tip 3b ÇH tanısı saptandı. ÇH saptanan DS'lu çocuklarda, korelasyon analizinde, hipotiroidizm (p0,03) ve diyare (p0,04) görülmesi anlamlı olarak ilişkili idi. DS'lu hastalarda, ishal ÇH görülme riskini 1,5 kat (0,67-3,34) artırırken, hipotiroidizmin 2.75 kat (0.55-13.67) arttırdığı saptandı. Sonuç: Klinisyenler, DS'li çocuklarda özellikle diyare ve / veya hipotiroidi varlığında ÇH’nı göz önünde bulundurmalıdır.
Down sendromlu çocuklarda gastrointestinal bulgular: Çölyak hastalığı için erken bir belirti var mı?
Keywords: Genel ve Dahili Tıp